INVESTIGATION OF THE CREEP EFFECT ON THE STRESS-STRAIN STATE ON TIMBER-REINFORCED CONCRETE MULTISTOREY BUILDINGS (Collection of scientific works «Modern structures of metal and wood», 2022)
One  of  the  modern  directions  in  construction  is  the  development  of  multistorey buildings, in which the main part of the structural elements is made of timber, and spatial stability is provided by reinforced concrete diaphragms or a stiffening core. A possible problem when using different materials in load-bearing structures is a significant difference in deformation characteristics and the effect of creep. The article presents the results of theoretical studies of the effect of concrete and wood creep on  the  stress-strain  state  of  timber-reinforced  concrete  multistorey  buildings.  A  square  in  plan prototype building with a frame system, load-bearing timber structures (glued laminated timber and LVL) and a reinforced concrete stiffening core was taken for the analysis. The number of floors was varied from 5 to 20 (the height of the options under consideration was 15-60 m). To take into account the creep of concrete, the Eurocode EN 1992-1-1 model was used, and the T. Toratti model of an elastic-viscous-plastic body was adopted for timber. When determining the creep characteristics, the conditions corresponding to service class 1 (55% relative humidity) and 2 (65% relative humidity) were considered. It has been established that during 50 years, the values of vertical displacements obtained taking into  account  creep  increase  several  times  compared  to  the  results  for  the  elastic  model:  under conditions of service class 1 by 2.6–3.7 times for laminated timber columns; by 1.8-3.1 times for LVL columns and by 3.3-3.4 times for reinforced concrete stiffening core; under the conditions of service class 2 by 2.4-3.7 times for laminated timber columns; by 1.8-2.9 times for LVL columns and by 3.05-3.15 times for reinforced concrete core. An  analysis  of  the  nature  of  the  deformation  of  the  considered  variants  showed  that  the magnitude of vertical displacements differs significantly for timber columns and a reinforced concrete stiffening  core.  Non-uniform  deformation  of  vertical  structures  causes  a  redistribution  of  forces between  the  frame  elements,  leads  to  a  skew  of  the  storey  and  the  appearance  of  additional longitudinal tensile forces in the floor beams.